Laparoscopic Versus Open Surgical Outcomes Repair For Inguinal Hernia- A Combined Prospective And Retrospective Cohort Study - Md Saiful Islam; Sayem Al Monsur Faizi; Mohammad Ziaur Rahman; Rana Jahangir Alam; Md. Jahangir Hossain; A. K. Al Miraj (International Journal of Medical Research and Review, 2024)
Inguinal hernias are common and have become a common surgical problem. In recent decades, the nature of their treatment has changed and new research is constantly being conducted in this field.  To find out the assessment the laparoscopic versus open surgical outcomes repair for inguinal hernia. A combined Prospective and retrospective Cohort study was carried out February 2023 to March 2024 in Department of General Surgery BSMMU. The sample size was two hundred for each arm; patients aged 18 and above without factors pre-disposing to recurrence were included in the study. The subjects were followed up for a period of one year at the end of which primary outcome assessed was recurrence. A number of secondary outcomes such as hematoma, persistent pain and return to regular activity were also assessed. Among the 100 individuals analyzed, 75 (75%) were male patients, with the majority of them falling between the ages of 41 and 55. In contrast to the open group of patients, the laparoscopic group experienced a significant increase in operative time with a highly significant statistical difference (p<0.0001), and the laparoscopic group experienced a significant decrease in post-operative pain score with an insignificant p-value. A significant statistical difference (p<0.005) was estimated among the laparoscopic and open groups of patients in terms of post-operative hospitalization. Returning to normal activities was significantly different for laparoscopic patients relative to the open group (p-value<0.001). With a high level of significance of p<0.001, laparoscopic hernia repair required less time to recover before returning to normal activities than open hernia repair (p<0.005). However, we observed that 90% of the recurrences in the laparoscopic arm were at the hands of surgeons with less than five years’ experience in laparoscopic surgery which was statistically highly significant (P value = 0.00). In the open arm however, the surgeons’ experience did not alter the outcome significantly (P value = 0.341). Thus, laparoscopic repair for inguinal hernia is a safe alternative in the hands of experienced laparoscopic surgeons.